Implementasi E-Government dalam Rekrutmen Peserta Pelatihan di UPT BLP2TK Surabaya - Lestari, Qawiyuni Putri; Nafiah, Binti Azizatun (Innovative: Journal Of Social Science Research, 2025)
Implementing e-government is an effort to increase efficiency, transparency and accountability in public services. This research aims to analyze the implementation of e-government in the process of recruiting training participants at the Technical Training Unit of the Surabaya Workforce Productivity Development Training Center (UPT BLP2TK) Manpower and Transmigration Service of East Java Province using google forms and evaluating the GEMAS-PRO (Massive Productivity Movement application) which was previously used, but is no longer operational. The results show that the use of google forms is quite effective in meeting basic administrative needs, but is less than optimal in several more complex aspects, such as managing participant data in an integrated manner. Evaluation of the GEMAS-PRO application has great potential to support digital transformation, but needs to be supported by adequate budget allocation and better sustainability strategies